Electric field enhancement effect on Raman spectra in two-dimensional MoSi2N4, TiSi2N4 and MoGe2As4 monolayers. (15th December 2022) - Deng, Zexiang
Abstract: Characterizing two-dimensional (2D) layered materials in the monolayer limit is key to discovering their new phenomena and unusual properties. We theoretically predict the electric field modulated Raman spectra of 2D MoSi 2 N 4, TiSi 2 N 4 and MoGe 2 As 4 monolayers, with two kinds of laser lines (532 and 633 nm). Based on the Raman tensor, we have calculated the angle-dependent Raman intensities of the major Raman peak ( A 1 ′ 1 ) in MoSi 2 N 4, TiSi 2 N 4 and MoGe 2 As 4 monolayers, locating at 1029 cm −1, 993 cm −1 and 317 cm −1, respectively. Applying the external electric field to MoSi 2 N 4 monolayer, the symmetry of D 3 h reduces to C 3 v, which results in more peaks of Raman-active modes found in the Raman spectra. As a result, besides E ′ and A 1 ′ modes, three other major Raman peaks ( A 1 ′ 1, A 1 ′ 2 and A 1 ′ 3 ) are found in MoSi 2 N 4, TiSi 2 N 4 and MoGe 2 As 4 monolayers, which can help us to distinguish the 2D MA 2 Z 4 materials. We find that the enhancement factor by external electric field can be up to 10 times. Moreover, the non-resonant Raman spectra peaks of doubly degenerate mode (E ′ ) and one-dimensional modes A 1 ′ and A 2 ″ in MoSi 2 N 4, TiSi 2 N 4 and MoGe 2 As 4 monolayer are calculated. These theoretical results of Raman spectra of MoSi 2 N 4 monolayer may provide theoretical guidelines for its utilization in crystal structure characterizations and optoelectric devices. Highlights: Angle-dependent Raman intensities in MoSi 2 N 4 (1029 cm −1 ), TiSi 2 N 4 (993 cm −1 ) and MoGe 2 As 4 (317 cm −1 ) monolayers. New Raman peaks induced by external electric field. The enhancement factor by external electric field can be up to 10.